2019
DOI: 10.11648/j.ijmb.20190404.12
|View full text |Cite
|
Sign up to set email alerts
|

Stability Study of the Pigment Extract from a Wild <i>Pycnoporus sanguineus</i>

Abstract: The stability of crude pigment of Pycnoporus sanguineus strain 28cc under different conditions was assessed. The strain was isolated from the fruit body of the fungus collected in Fenglin National Nature Reserves (China) and had been identified by morphological and rDNA-ITS based approach. The natural pigments were obtained from cultural liquid of submerged culture by adsorption of macro-porous resin (HPD-722) and eluted with 80% ethanol. The natural colorants had a characteristic absorption peak of 416nm (cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Among the tested wastes, the wood chip was found to be the best substrate not only giving a maximum pigment yield but also greatly promoting the growth of strain SYBC-L7. In the literature, most Pycnoporus species have been isolated and used as enzyme producers ( Tellez-Tellez et al, 2016 ), but few of them were used to produce pigment, which was shown in ( Supplementary Table S1 ; Eggert, 1997 ; Smania et al, 1997 ; Cruz-Munoz et al, 2015 ; Sutthisa and Sanoamuang, 2017 ; Zhang et al, 2019 ). However, our study is the first report, to our knowledge, on using agro-industrial waste, especially wood chips as a culture substrate for pigment production by Pycnoporus sanguineus SYBC-L7.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the tested wastes, the wood chip was found to be the best substrate not only giving a maximum pigment yield but also greatly promoting the growth of strain SYBC-L7. In the literature, most Pycnoporus species have been isolated and used as enzyme producers ( Tellez-Tellez et al, 2016 ), but few of them were used to produce pigment, which was shown in ( Supplementary Table S1 ; Eggert, 1997 ; Smania et al, 1997 ; Cruz-Munoz et al, 2015 ; Sutthisa and Sanoamuang, 2017 ; Zhang et al, 2019 ). However, our study is the first report, to our knowledge, on using agro-industrial waste, especially wood chips as a culture substrate for pigment production by Pycnoporus sanguineus SYBC-L7.…”
Section: Resultsmentioning
confidence: 99%
“…Pycnoporus sanguineus is one of the promising organisms for developing natural pigments, and it could produce various shades of red, orange, yellow, and brown color ( Zhang et al, 2019 ). These primary or secondary metabolites produced by Pycnoporus genus are different and depend on the species and culture conditions ( Cruz-Munoz et al, 2015 ; Tellez-Tellez et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of monovalent (Na + and K + ) and divalent (Ca 2+ and Mg 2+ ) did not give a significant shift in the spectrogram of the extract (Figure 2b). The absence of the shift caused by the addition of monovalent and divalent metal ions was also observed in various anthocyanin source extracts, such as blueberries (Wang et al, 2010) , red cabbage (Guo et al, 2017) , black peanuts (Shao et al, 2015) , Bunius antidesma (Mustika and Marpaung, 2020) , cyanidin-derived anthocyanin (Sigurdson et al, 2017;Sigurdson et al, 2016), Ribes nigrum (Buchweitz et al, 2013) , dark maize (Mei et al, 2014) , and fungus Pycnoporus sanguineus (Zhang et al, 2019) . In contrast, sodium (Na + ) enhances the color of malvidin-derived anthocyanin (Dangles and Brouillard, 1992;Figueiredo and Pina, 1994), potassium (K + ) increases the intensity of anthocyanin in red wine (Czibulya et al, 2015) , and calcium (Ca 2+ ) has a color-enhancing effect on blueberry anthocyanin (Li, 2014) and a slight impact on the color of red cabbage anthocyanin (Ratanapoompinyo et al, 2017) .…”
Section: The Effect Of the Metal Ions On The Spectrogrammentioning
confidence: 90%